If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2x + 4) + 1 = -13 Reorder the terms: -3(4 + 2x) + 1 = -13 (4 * -3 + 2x * -3) + 1 = -13 (-12 + -6x) + 1 = -13 Reorder the terms: -12 + 1 + -6x = -13 Combine like terms: -12 + 1 = -11 -11 + -6x = -13 Solving -11 + -6x = -13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + -6x = -13 + 11 Combine like terms: -11 + 11 = 0 0 + -6x = -13 + 11 -6x = -13 + 11 Combine like terms: -13 + 11 = -2 -6x = -2 Divide each side by '-6'. x = 0.3333333333 Simplifying x = 0.3333333333
| 3y-5=3-2y | | y+4=-21 | | x-3(x+1)=9 | | -12x=-4+28 | | 4t+1+4t-7t=6+6 | | 2x+15=2x-3x | | 24(4k+22)=24(4k+24) | | (2+i)+(-7+5i)= | | 7*(-6)*5*(-4)*3*(-2)*1*0= | | 36+104-7x=8x | | -4y+7=-5y+8 | | 1/4s=-5 | | X=19+4y | | 3x^2-2x=8x-8 | | 3f-4-5f=f+4+5 | | 15x^2=100 | | -20n+6(16+16n)=-12(n-8) | | 3y^2=-7-4 | | -21y=-765 | | 3n+18=-24 | | 2x^7/2x^3/13 | | 1/3(9x+5)=5(x-1)-6 | | 4b^2+(-7)b=0 | | 2a+6=a-8 | | f(x)=2x^2-5x-3 | | -3h+4.2=55-11h | | 6+(3x-3)=2 | | 3x+5-3x=4x-2 | | 3x+5-3x=4x-2 | | -10+p/9=-11 | | -9(x+6)=-54 | | 1/5s=2 |